Intravenous Lidocaine Versus Thoracic Epidural Analgesia: A Randomized Controlled Trial in Patients Undergoing Laparoscopic Colorectal Surgery Using an Enhanced Recovery Program. Issue 3 (1st April 2011) - Wongyingsinn, Mingkwan; Baldini, Gabriele; Charlebois, Patrick; Liberman, Sender; Stein, Barry; Carli, Franco
Abstract : Background and Objective: Laparoscopy, thoracic epidural analgesia, and enhanced recovery program (ERP) have been shown to be the major elements to facilitate the postoperative recovery strategy in open colorectal surgery. This study compared the effect of intraoperative and postoperative intravenous (IV) lidocaine infusion with thoracic epidural analgesia on postoperative restoration of bowel function in patients undergoing laparoscopic colorectal resection using an ERP. Methods: Sixty patients scheduled for elective laparoscopic colorectal surgery were prospectively randomized to receive either thoracic epidural analgesia (TEA group) or IV lidocaine infusion (IL group) (1 mg/kg per hour) with patient-controlled analgesia morphine for the first 48 hours after surgery. All patients received a similar ERP. The primary outcome was time to return of bowel function. Postoperative pain intensity, time out of bed, dietary intake, duration of hospital stay, and postoperative complications were also recorded. Results: Mean times and SD (95% confidence interval) to first flatus (TEA, 24 [SD, 11] [19-29] hrs vs IL, 27 [SD, 12] [22-32] hrs) and to bowel movements (TEA, 44 ±19 [35-52] hrs vs IL, 43 [SD, 20] [34-51] hrs) were similar in both groups ( P = 0.887). Thoracic epidural analgesia provided better analgesia in patients undergoing rectal surgery. Time out of bed and dietary intake were similar. Patients in the TEA and IL groups were discharged on median day 3 (interquartile range, 3-4 days), P = 0.744. Sixty percent of patients in both groups left the hospital on day 3. Conclusions: Intraoperative and postoperative IV infusion of lidocaine in patients undergoing laparoscopic colorectal resection using an ERP had a similar impact on bowel function compared with thoracic epidural analgesia.